Pengaruh Aplikasi Kotoran Walet dan Urea Terhadap Berat Kering dan Serapan Nitrogen Tanaman Sawi (Brassica juncea L.) pada Lahan Pasang Surut - Annisa Yuliani Dewi; Afiah Hayati; Hairil Ifansyah (Universitas Lambung Mangkurat, 2020)
The purpose of this study was determine whether the application of swallow manure is able to replace the role of urea fertilizer in dry weight and nitrogen uptake of mustard plants on tidal land and to find out whether there is an interaction between manure and urea in dry weight and nitrogen uptake of mustard plants in tidal land . The study was carried out on Jalan Pemuda Km 9.5 Desa Teluk Palingit (Pelundu), Kec. Pulau Petak Kab. Kapuas. The research will start in May 2019 - October 2019. The research design uses Completely Randomized Design (CRD) factorial 2 factors. Factor I: Swallow manure (W) consisting of 4 levels of treatment, namely W0 = control, W0.5 = 0.5 tons ha-1, W1 = 1 ton ha-1, W2 = 2 tons ha-1, and factor II: urea (U) fertilizer consists of U0 = 0 kg ha-1, U25 = 25 kg ha-1, U50 = 50 kg ha-1, U100 = 100 kg ha-1. Each treatment was repeated 3 times, so as to get 48 experimental units. Application of swallow manure 1 tons ha1 can replace the role of urea fertilizer with a dose of 50 kg ha-1 and 100 kg ha-1 in increasing the dry weight and nitrogen uptake of mustard plants in tidal land, and the combination of swallow manure with a dose of 1 tons ha-1 and 50 kg ha-1 urea fertilizer can increase the dry weight and nitrogen uptake of mustard plants on tidal land.